Implementation of the Balanced Scorecard (BSC) in Measuring Community Health Center Performance: A Case Study in West Obi District, South Halmahera Regency - Naswan Hadilia; Aspiati A. Samiun (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This study aims to assess organizational performance using the Balanced Scorecard approach, which encompasses four perspectives: financial, customer, internal business processes, and growth and learning. The assessment was conducted qualitatively by analyzing the average value, score, and performance category for each perspective. The results indicate that overall organizational performance is in the good category, although there is variation in achievement across perspectives. The financial perspective obtained an average score of 79, categorized as good, indicating effective and efficient financial management. The customer perspective recorded an average score of 76.8, categorized as good, reflecting that service quality and user satisfaction levels have been met. The internal business process perspective demonstrated the most outstanding performance, with an average score of 73, categorized as very good, indicating that operational processes and work procedures are running optimally. Meanwhile, the growth and learning perspective obtained the highest average score, 80.4, categorized as good, demonstrating the organization's commitment to human resource development, learning, and innovation. Overall, the results of this study confirm that the Jikohai Community Health Center in West Obi District has good performance with the main strengths in the aspects of internal processes and learning, but a continuous improvement strategy is still needed so that balance and optimization of performance between perspectives can be achieved.